Brain Metastases: A Modern Multidisciplinary Approach. (12th March 2021) - O'Halloran, Philip J.; Gutierrez, Enrique; Kalyvas, Aristotle; Mohan, Nilesh; Atallah, Soha; Kalia, Suneil; Millar, Barbara-Ann; Laperriere, Normand; Conrad, Tatiana; Zadeh, Gelareh; Bernstein, Mark; Shultz, David B.; et al.
ABSTRACT: Brain metastases (BM) are the most common intracranial neoplasm and represent a major clinical challenge across many medical disciplines. The incidence of BM is increasing, largely due to improvements in primary disease therapeutics conferring greater systemic control, and advancements in neuroimaging techniques and availability leading to earlier diagnosis. In recent years, the landscape of BM treatment has changed significantly with the advent of personalized targeted chemotherapies and immunotherapy, the adoption of focal radiotherapy (RT) for higher intracranial disease burden, and the implementation of new surgical strategies. The increasing permutations of options available for the treatment of patients diagnosed with BM necessitate coordinated care by a multidisciplinary team. This review discusses the current treatment regimens for BM as well as examines the salient features of a modern multidisciplinary approach.